Tarombo Suku Batak Toba sebagai Sumber Belajar Sejarah untuk Meningkatkan Kesadaran Sejarah - Tona Martua Simatupang; Didin Saripudin; Tarunasena Tarunasena (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The Tarombo of the Batak Toba people, as a genealogical record, holds significant historical value related to the origins, social structure, and culture of the Batak Toba community. However, its use as a historical learning resource in schools remains underutilized. The main issue addressed in this study is how the Tarombo can be utilized as a source of historical learning to enhance students' historical awareness. This research aims to identify the potential of the Tarombo as an effective educational tool and its relevance in enriching students' historical understanding and increasing historical awareness. The study employs a literature review methodology, analyzing various written sources related to Tarombo, Batak Toba culture, and historical learning theories. The findings indicate that the Tarombo can serve as a valuable learning resource, providing local historical insights that help students understand the social and cultural dynamics of the Batak Toba people. By incorporating Tarombo into history lessons, students not only learn about their family histories but also strengthen their historical awareness and cultural identity. Thus, the Tarombo can be an important tool in fostering a love for the nation and enriching cultural knowledge in history education.